(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The purpose of the article is to expose the main differences and similarities between the common law legal system and the civil law system, pointing out the approximation between these systems and the influence of the constitutionalization of law in the civil law system. It considers it necessary for national law itself to make a critical comparison between the two systems on the basis of their historical origin and their consequent evolution as they approach and are influenced by the globalization of law today. The intercommunication between the systems causes reflexes in several countries, including Brazil. Thus, the opportunity of this historical recovery is indispensable to understand the changes that are taking place in the systems in view of the approximation between them and the search for effective legal certainty that accompanies the evolution of society.